Karakteristik Peserta Didik Ditinjau Pada Tingkat Madrasah Ibtida’iyah Atau Sekolah Dasar Pada Mata Pelajaran Ski - Maylinda Safitri, Maylinda Safitri; Ari Susetiyo; Shahzadi Hina Sain, Shahzadi Hina Sain (Universitas Garut, 2025)
Education primarily aims to acquire knowledge and to shape activities that influence an individual’s development, transformation, character, and morality. The process of education for children up to adolescence takes place through various dynamic and ever-changing stages. The teaching of Islamic Cultural History (SKI) in elementary schools is intended to instill an understanding of the values embedded in the history of Islam, while also encouraging students to apply those values in their daily lives. Furthermore, SKI learning helps students to recognize, comprehend, and internalize the heritage of Islamic civilization, while fostering intellectual growth, character formation, and personality development. Through SKI, learners are also guided to develop an awareness of the importance of studying the foundations of Islamic teachings, values, and norms, as well as to emulate the struggles and achievements of Islamic figures in defending and spreading the religion of Islam. Keywords: Character, Learners, Islamic Elementary School, Islamic Cultural History (SKI)